Macleayins A From Macleaya Promotes Cell Apoptosis Through Wnt/β-Catenin Signaling Pathway and Inhibits Proliferation, Migration, and Invasion in Cervical Cancer HeLa Cells - Sai, Chunmei; Qin, Wei; Meng, Junyu; Gao, Li-Na; Huang, Lufen; Zhang, Zhen; Wang, Huannan; Chen, Haixia; Yan, Chaohua (Frontiers in Pharmacology, 2021)
Macleayins A (MA) was a novel compound isolated from Macleaya cordata (Willd.) R. Br. and Macleaya microcarpa (Maxim.) Fedde. The plant species are the member of Papaveraceae family and have been used traditionally for diverse therapeutic purposes. According to the reported studies, the chemicals constituents, as well as crude extracts of these plants could attenuate the proliferation of several cancer cell lines, such as HL-60, A549, HepG2, and MCF-7, etc. The current study aimed to investigate the anti-cervical cancer activity of MA and its related molecular mechanism. Isolation of MA was carried out using various column chromatographic methods, and its structure was elucidated with 1H NMR. The cytotoxicity of MA was determined against HeLa cell-lines via CCK-8 assay. The cell proliferation, apoptosis, cell cycle, migration, and invasion were measured by EdU labeling, Annexin-V APC/7-AAD double staining, PI staining, transwell assay, respectively. The protein expression levels of c-Myc, β-catenin, cyclin D1 and MMP-7 in the cells were evaluated by western blotting. The Wnt/β-catenin signaling cascade activation was verified using the Dual-Glo® Luciferase assay. We found that MA inhibited the growth of HeLa cells at 72 h (IC50 = 26.88 µM) via inducing apoptotic process, reduced the proliferation rate by 29.89%, and declined the numbers of invasive and migrating cells by 180 as compared to the untreated group. It arrested the cell cycle at the G1 phase and its treatment inhibited the expression of related proteins c-Myc, β-catenin, cyclin D1 and MMP-7 in the Wnt/β-catenin signaling cascade. Further, the Wnt/β-catenin signaling cascade activation in MA treated HeLa cells was attenuated in a dose-dependent manner. These findings demonstrate the anticancer effects of MA on mechanistic level, thus providing a basis for MA to become a potential resistance cervical carcinoma candidate drug.